The Effect of Digital Banking, Capital Adequacy Ratio, and Operational Efficiency on the Financial Performance of Islamic Commercial Banks in Indonesia - Rahma Sri Endah Mahesti; Hardiyanto Wibowo; Bima Cinintya Pratama; Nur Isna Inayati (Indonesian Journal of Advanced Research, 2026)
This study is motivated by an apparent contradiction in Indonesian Islamic banking: the number of digital banking users has grown steadily, yet the profitability of Islamic commercial banks (Bank Umum Syariah, BUS) has remained volatile. Prior evidence on the determinants of Islamic bank profitability also remains inconclusive. This study therefore examines the effect of digital banking, capital adequacy (CAR), and operational efficiency (BOPO) on financial performance proxied by return on assets (ROA). Using a quantitative approach, secondary data were collected from the annual reports of 13 Islamic commercial banks in Indonesia over the 2019–2023 period, selected through purposive sampling, yielding 55 bank-year observations for analysis. Data were analysed using multiple linear regression in IBM SPSS Statistics, preceded by classical assumption testing. The results show that digital banking has no significant effect on ROA; CAR has a positive and significant effect on ROA, so the hypothesis predicting a negative effect is not supported; and BOPO has a negative and significant effect on ROA. Jointly, the three variables significantly explain variation in ROA. These findings indicate that, over the observed period, capital adequacy and cost efficiency were the dominant internal determinants of Islamic bank profitability, whereas digital adoption measured by user numbers had not yet translated into short-term earnings. The study contributes to the financial intermediation literature by showing that digital adoption creates economic value only when it is converted into transactions, fee income, or cost savings, and offers practical guidance for bank management and regulators.